KERAGAMAN JENIS SATWA BURUNG BERDASARKAN KETINGGIAN TEMPAT PADA HUTAN DESA RAMBATU KABUPATEN SERAM BAGIAN BARAT PROVINSI MALUKU Bird Diversity Based On Forest Height In Rambatu On West Seram Regency On Moluccas Province - Anthonia Tuhumury; L. Latupapua (Jurnal Hutan Tropis, 2014)
Rambatu is one of villages located in the mountainous area in the subdistrict of Inamosol, West Seram regency which has a lot of agricultural and forestry crops so it is a good habitat for birds. Rambatu villages has several species of birds, among others: Cikukua Seram (Philemon subcorniculatus), Kasturi (Lorius garrulus), Nuri Maluku (Eos bornea), Pombo Hutan (Ducula sp), and Nuri Pipi Merah (Geoffroyus geoffroyi). This study aims to determine the diversity of bird species in some altitude and determine the effect of vegetation as habitat on diversityof bird species in the Rambatu forest, Subdistric of Inamosol,West Seram Regency. Bird observation method used in thr VCP (Variable Circular Plot) method and the observations of vegetation is carried out based on the method of ploted lines analysis on the observation tracks. The diversity of bird species found in the Rambatu forestat an altitude 250, 500 and 750 m above sea level (asl) as many as 23 species. Forest at an altitude of 250 m above sea level has H’ = 1,117 by 19 species of birds were found; forest at an altitude of 500 m above sea level has H’ = 0.981 by 18 species of birds, while the forest at an 750 m above sea level has H’ = 0.823 by 11 species of birds. Regression analysis showed that the relationship between density and diversity of vegetation variables did not significantly affect the diversity of bird species, but if the forests conditions are not disturbed where vegetation density and diversity is maintained then will be able to increase the diversity of bird species. Keywords: Bird Species Biodiversity, Vegetation